Exploring the relationship between trunk muscles and lower limb injuries in Australian badminton players - Hides, J. A.; Mendis, M. D.; Leung, F.; Grantham, B.; Coombes, B. (Journal of Biomechanics, 2024)
Due to its dynamic nature, lower limb injuries are common in badminton. Overuse injuries of the knee, including tendon related conditions, are the most common. During jumping and landing, force transference and dissipation through the trunk is required, with the trunk muscles playing a vital role. However, the relationship between knee pain and the ability to voluntarily contract the trunk muscles has not yet been explored in badminton players. A cross-sectional study of Australian badminton players was therefore conducted. Players performed a single leg decline squat to identify those with knee pain. Ultrasound imaging was used to image and measure the size of the multifidus and quadratus lumborum, and the ability to contract the abdominal and multifidus muscles. Voluntary contraction of the trunk muscles was conducted with the subjects lying down. Independent samples T-Tests were performed to test for between group differences. Badminton players with knee pain had larger quadratus lumborum muscles and demonstrated a greater change in muscle thickness from the rested to contracted state. While we cannot comment on causation or direction, over co-contraction of trunk muscles has been shown in other studies to be associated with increased ground reaction forces on landing. Motor control training has been successfully used in other conditions to modify trunk muscle recruitment patterns and may therefore potentially represent a useful approach for badminton players.